2013
DOI: 10.4067/s0717-95022013000200029
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Effect of Vitamin E on Oocytes Apoptosis in Morphine-treated Mice

Abstract: Objective(s)Cigarette and nicotine enhances embryogenesis, fertility, pregnancy loss and ultrastructure alterations of oocyte. This study was performed to determine the effect of daily supplementation of vitamin E on oocytes apoptosis in nicotine-treated mice.Materials and MethodsIn this experimental study, 24 NMARI adult female mice were randomly allocated into four experimental groups. For 30 days, animals in control group (C) were received saline through subcutaneous injection, group I received vitamin E (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…ROS play a fundamental role in intracellular pathways, which involve several reproductive physiological functions including the maturation of follicles and oocyte, ovulation, ovarian steroidogenesis, fertilization, embryo development and pregnancy (Agarwal et al 2005, Fujii et al 2005. Overproduction of ROS or imbalance between ROS levels and antioxidant defense system can also lead to cell injury and apoptosis (Finkel 2011, Asadi et al 2013. ROS generation is stimulated during ovarian tissue cryopreservation (Abedelahi et al 2010), and it is a primary mechanism that causes DNA damage during freezing-thawing process (Tremellen 2008).…”
Section: Introductionmentioning
confidence: 99%
“…ROS play a fundamental role in intracellular pathways, which involve several reproductive physiological functions including the maturation of follicles and oocyte, ovulation, ovarian steroidogenesis, fertilization, embryo development and pregnancy (Agarwal et al 2005, Fujii et al 2005. Overproduction of ROS or imbalance between ROS levels and antioxidant defense system can also lead to cell injury and apoptosis (Finkel 2011, Asadi et al 2013. ROS generation is stimulated during ovarian tissue cryopreservation (Abedelahi et al 2010), and it is a primary mechanism that causes DNA damage during freezing-thawing process (Tremellen 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ability of antioxidant defense to ROS is important for protecting tissues from oxidative damage. Vitamin E, referred to as the plant-derived and lipid-soluble antioxidants, plays an important role in reproduction through reducing oocyte apoptosis [36], and promoting oocyte maturation, endometrium proliferation and luteal function [37].…”
Section: Discussionmentioning
confidence: 99%
“…It can prevent biological damage and possess the antioxidant property of unsaturated fatty acids which can stabilize cell membranes [38]. In one study, it was found that supplementation with vitamin E reduces the oocyte apoptosis in mice treated orally with 60 mg/kg/day nicotine [36]. The effects of antioxidants on apoptosis cell specific.…”
Section: Discussionmentioning
confidence: 99%
“…TCP was discovered earlier in 1928 and TCT was discovered a few years later in 1946. The lower publications might be due to its lower availability in nature and therefore not easily available for research studies [1,2]. Over the years, attention was therefore mainly focused on TCP and substantial amount of money and time was invested in its exploration, development, application and commercialization.…”
Section: Tocotrienols As Antioxidantsmentioning
confidence: 99%